Resilience Of Efficacy Perawat Berbasis Tingkat Stres dan Kepuasan Kerja - Nian Afrian Nuari (Jurnal Kesehatan, 2017)
A nurse must be able to balance the various stressors obtained in the work environment because they have to provide professional services to patients. This requires personal factors inherent in the nurse so as to adapt to stressful conditions. Internal factors include the ability to withstand the problem (resilience of efficacy). The purpose of this study was to determine the correlation resilience of efficacy with the level of stress and job satisfaction nurses in RS X. The research method was a correlational study with purposive sampling and sample size of 30 respondents. The instruments were used questionnaires then analyzed with Spearman rho test. Based on the result, the majority (56,7%) respondents have high category resilience of efficacy, the majority (80%) have light work stress and most of them (93,3%) have high job satisfaction. The results of research obtained, resilience of efficacy with nurse work stress level (p=0,039, cc=-0,393), resilience of efficacy with nurse job satisfaction (p-value=0,007, and cc=0,469). This means there was a correlation between the resilience of efficacy with work stress and nurse job satisfaction. It is expected that nurses need to do a good coping strategy for overcoming the problems found. The higher the resilience of efficacy the lower the stress level will be and it will increase the nurse's comfort in working so that it can improve job satisfaction.